Patient safety: a novel flipped classroom curriculum for family medicine residents - Jattan, Aaron; Suss, Roger (Canadian Medical Education Journal, 2024)
Implication Statement Addressing patient safety incidents is a complicated and challenging issue for physicians. At present, there is little training in residency programs to help prepare learners to tackle situations where harm arises as a result of healthcare delivery. In response to new accreditation mandates, we piloted a flipped classroom patient safety curriculum to help train family medicine residents to identify and address patient safety incidents in practice. Family medicine programs could consider similar case-based training for their learners to help prepare them to respond to these events and address contributory factors.